Perancangan Bisnis untuk Boardgame "Conquest Nusantara" - Richie Leonardo; Shienny Megawati Sutanto (Jurnal Vicidi, 2018)
This research contains the business idea of “Conquest Nusantara” Board Game. The methods which are used in this research are the methods of collecting data with qualitatively and quantitatively by data extraction through interviews with expert and extreme users, questionnaries to the potential customers, and literature studies. This research have purpose to find out growth and people responses for board game, and for find out how to designing and responses from people about “Conquest Nusantara” Board Game which have local theme and historical education element. This research concludes that “Conquest Nusantara” Board Game which have local theme and historical education element receive positive respons and can be effective solution to solve problem for game that aside from just game but can also be means of learning about Indonesia history.